Evaluation of Distal Extracranial Internal Carotid Artery by Transoral Carotid Ultrasonography in Patients with Severe Carotid Stenosis - Kishikawa, Kazuhiro; Kamouchi, Masahiro; Okada, Yasushi; Inoue, Tooru; Ibayashi, Setsuro; Iida, Mitsuo (American Journal of Neuroradiology, 2002)
BACKGROUND AND PURPOSE: Conventional ultrasonography techniques do not allow visualization of the distal cervical segment of the internal carotid artery (ICA). In a study of patients with severe ICA stenosis, we performed transoral carotid ultrasonography (TOCU) to assess its ability to image this segment of the artery.METHODS: The study participants consisted of 20 consecutive patients who had severe carotid stenosis and who underwent carotid endarterectomy between 1999 and 2000. TOCU, conventional carotid ultrasonography, and cerebral angiography were prospectively performed before and after carotid endarterectomy.RESULTS: In all patients, the distal portion of the ICA could be clearly detected by B mode using TOCU and no plaque was observed. The diameter of the distal portion of the ICA significantly increased after carotid endarterectomy (3.9 ± 0.5 mm [mean ± SD]), compared with before (3.5 ± 0.8 mm), when it was estimated by TOCU (P < .01). In seven patients, the postoperative diameter of the distal ICA increased >10%. The mean increase in the postoperative diameter was estimated to be 15.0 ± 23.0% by TOCU, which significantly correlated with the findings (23.9 ± 33.7%) based on cerebral angiography (P < .01). The diameter increased >10% postoperatively in 71% of the patients with the degree of cross-sectional stenosis >95% as shown by carotid ultrasonography and in 86% of the patients whose preoperative diameter was <3.0 mm.CONCLUSION: TOCU provides additional information regarding the characteristics of the distal ICA that can be obtained neither by conventional carotid ultrasonography nor by angiography.